PERJANJIAN JUAL BELI MELALUI APLIKASI ONLINE OLEH ANAK DIBAWAH UMUR - Abdul Wahid; Rohadi Rohadi; Siti Alisah (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2022)
One of the conditions for the validity of the agreement mentioned above is legal competence. Legal competence in question is that if a person commits a legal act, he can be subject to certain legal actions against him. One of the conditions for a person to be legally proficient is that he is an adult. Adults here are seen from the age limit determined by each legal discipline. Failure to fulfill the requirements for legal competence will result in the cancellation of the agreement being requested by the judge. So that the agreement can be canceled at the will of one of the parties but if the parties wish to continue, the sale and purchase agreement can still be carried out provided that the terms of the agreement are valid according to Article 1320. This type of research is normative juridical, namely the type of research conducted by studying norms - existing norms or laws and regulations related to the issues discussed. The legal force of agreements made by minors in e-commerce transactions can still be considered valid. However, this can later cause legal problems for minors who carry out e-commerce transactions, because the agreement is weak. After all, it does not fully meet the legal requirements of the agreement law based on Article 1320 of the Civil Code, namely the subjective requirements. While the legal consequences of an online sale and purchase agreement (e-commerce) carried out by minors, which is the agreement can be canceled. This is different from being null and void because null and void can only be done if the objective conditions are not met while the minors are included in the subjective conditions. However, as long as the parties are not concerned about the non-fulfillment of one of the legal conditions of the agreement according to Article 1320 of the Civil Code and the parties continue to carry out the agreement they have made, the contract is made to remain valid so that it is binding and becomes law. Keywords: Agreements, Purchases, Online Applications, Minors.